Characterization of Sand Proppant and Its Improvement via Polyurethane Coating - Fitrah Abu Bakar, Noor; Norhidayah Abdullah Zawawi, Siti; Mohd Zin, Rohani; Abdul Rahman, Norazah; Kassim Shaari, Norin (International Journal of Engineering and Technology, 2018)
Characterization of sand as proppant, its improvement using a simple polyurethane coating technique without heating and its coating evaluation using impingement test were investigated. Sand samples were obtained from eight locations in Malaysia beaches. Several important properties of proppant namely particle size distribution, density, turbidity, acid solubility, roundness and sphericity, and crush resistance were determined. Sample from Pantai Bachok, Kelantan showed the best characteristics of proppant that complies with the specifications set by API and ISO except for acid solubility and crush resistance. The proppant sample size of 20/40 mesh size was with density of 1.67g/cm3, turbidity of 162 FTU, acid solubility of 2.8%, roundness and sphericity of 0.46 and 0.7, respectively. For crush testing, all sand samples can only withstand pressure up to 2000 psi. Polyurethane (PU) formulated from palm oil-based polyols has been used to coat the sand particles to improve acid solubility and crush resistance of the beach sand.  The PU-coated sands from Pantai Bachok, Kelantan showed better acid solubility of only 0.38% and crush resistance of approximately 10% at 4000 psi than the uncoated ones.  The impingement test showed that PU-coated sands gave less impact towards metal target and lower metal losses.